2000
DOI: 10.1590/s0100-879x2000001200015
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen consumption of rats with broad intestinal resection

Abstract: The study was performed to investigate possible alterations in oxygen consumption in an animal model with broad intestinal resection. Oxygen consumption and the thermal effect of a short meal were measured in rats subjected to short bowel syndrome. Four groups of rats were used. Group I was the control group, group II was sham operated, group III was submitted to 80% jejunum-ileum resection, and group IV was submitted to 80% jejunum-ileum resection with colon interposition. Ninety days after surgery, oxygen co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Unfortunately, only 3 of the 11 patients in the parenteral nutrition group had SBS with the other patients in this cohort having intractable diarrhea or intestinal dysmotility. Finally, in a study involving rats subjected to 80% SBS or Sham operations, no differences were identified in EE as recorded by indirect calorimetry [21]. Similar to the others studies cited above, these animals were studied at a singular postoperative time point (90 days), which was well beyond the early phases of intestinal adaptation.…”
Section: Discussionmentioning
confidence: 92%
“…Unfortunately, only 3 of the 11 patients in the parenteral nutrition group had SBS with the other patients in this cohort having intractable diarrhea or intestinal dysmotility. Finally, in a study involving rats subjected to 80% SBS or Sham operations, no differences were identified in EE as recorded by indirect calorimetry [21]. Similar to the others studies cited above, these animals were studied at a singular postoperative time point (90 days), which was well beyond the early phases of intestinal adaptation.…”
Section: Discussionmentioning
confidence: 92%
“…It is important to note that not all surgical manipulations of the GI tract lead to increased EE. Rats and humans with short bowel syndrome and associated malabsorption exhibit no change in TEE and REE (40,41). We have recently performed EE measurements in rats that have undergone other GIWLS procedures (sleeve gastrectomy and gastric banding) in which the only alteration is the reduction of stomach size, and we observed that these manipulations had no significant effect on EE (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…42 The raised energy expenditure after GBP appears be specific for this intervention, as not all surgical manipulations of the gastrointestinal tract lead to increased energy expenditure; rats and humans with short bowel syndrome and associated malabsorption exhibit no change in total and/or resting energy expenditure. 52,53 Moreover, measurements of energy expenditure in rat models of sleeve gastrectomy and gastric banding in which the only alteration is the reduction of stomach size revealed no significant effect on energy expenditure. 41,54 Consequently, it seems that increased energy expenditure is associated with procedures that involve a rearranged gastrointestinal anatomy to cause duodenal exclusion from the alimentary flow or accelerated intestinal exposure to undigested nutrients (e.g., GBP).…”
Section: Discussionmentioning
confidence: 98%